Managerial economics - Hirschey, Mark.; Pappas, James L.; Whigham, David (London : Dryden Press, 1995)
Provides a solid foundation of economic understanding for use in managerial decision making.One key feature of this market-leading text is its attempt to depict the firm as a cohesive, unified organization. Also presents those aspects of economic theory and analysis that are most relevant to students of business administration in an intuitive calculus-based or noncalculus-based format, depending upon the preferences of the instructor.
Includes bibliographical references and index.
oif 06/03/15
Loan
Keywords: Managerial economics